Edwin Thumbooâ€™s â€œDifferenceâ€: Some Dilemmas of Post-colonial Creativity - Kandiah, Perth, Australia, Thiru (Asiatic: IIUM Journal of English Language and Literature, 2013)
Despite Edwin Thumbooâ€™s iconic status within the modern Singaporean artistic scene, observation of the highly vibrant creative and critical activity that has gone on/is still going on on that scene suggests, somewhat ironically, that he and his fellow artistes have throughout been proceeding, unrecognised, along significantly divergent paths. The paper argues that what Thumboo has to offer his fellow artistes/critics will remind them of things they cannot afford to forget, as they seem to have, if their work is to address what might be considered the main challenge of post-colonial creativity, namely, that of fashioning, out of their own available (modern and traditional) resources a distinct contemporary Singaporean creative voice, the voice through which they will be able to liberate themselves and their people from the epistemological, cultural and other forms of hegemony under which, through its interpellations, the dominant empire/capitalism constructed hierarchised global order is seeking to draw them. The paper supports its argument by appending an earlier unpublished paper by the author that supplies a theorised examination of activity in the Singapore theatre during the headiest days of its coming alive that predicts to its present state.